2009
DOI: 10.1161/strokeaha.109.553248
|View full text |Cite
|
Sign up to set email alerts
|

Intense Correlation Between Brain Infarction and Protein-Conjugated Acrolein

Abstract: Background and Purpose-We recently found that increases in plasma levels of protein-conjugated acrolein and polyamine oxidases, enzymes that produce acrolein, are good markers for stroke. The aim of this study was to determine whether the level of protein-conjugated acrolein is increased and levels of spermine and spermidine, the substrates of acrolein production, are decreased at the locus of infarction. Methods-A unilateral infarction was induced in mouse brain by photoinduction after injection of Rose Benga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 86 publications
(63 citation statements)
references
References 30 publications
1
62
0
Order By: Relevance
“…If it is possible to protect or delay the aggravation of brain infarction and dementia, it could greatly contribute to the maintenance of quality of life of the elderly. We have previously reported that a toxic compound, acrolein, becomes a good biomarker for brain infarction 11 and dementia. 23 Thus, we looked for compounds that decrease the level of acrolein during brain damage and do not have severe side effects.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…If it is possible to protect or delay the aggravation of brain infarction and dementia, it could greatly contribute to the maintenance of quality of life of the elderly. We have previously reported that a toxic compound, acrolein, becomes a good biomarker for brain infarction 11 and dementia. 23 Thus, we looked for compounds that decrease the level of acrolein during brain damage and do not have severe side effects.…”
Section: Discussionmentioning
confidence: 99%
“…acrolein scavengers, such as N-acetylcysteine (NAC) 11 and N-benzylhydroxylamine, 12 decreased the size of brain infarction using photochemically induced thrombosis (PIT) mice.…”
Section: Strokementioning
confidence: 99%
See 3 more Smart Citations